Investigation of Contact Properties and Device Performance for Bifacial Double-Side Textured Silicon Solar Cells With Polysilicon Based Passivating Contacts - Pradeep Padhamnath; John Derek D. Arcebal; Sagnik Dasgupta; Gabby De Luna; Ajeet Rohatgi; Armin G. Aberle (SiliconPV Conference Proceedings)
We investigate the impact of the surface morphology on the contact properties of phosphorus doped poly-Si layers. If the poly-Si layer on a textured surface remains intact after high-temperature metallization using a fire-through (FT) silver (Ag) paste, the J0,metal is not expected to increase significantly while the specific contact resistivity can improve with a textured surface. The contact properties of the FT Ag contacts to n+ poly-Si deposited on both textured and planar surfaces are investigated by measuring and evaluating ρc and J0,metal. The reasons for differences in contact resistance and recombination are further investigated with SEM imaging. Solar cells with n-type polysilicon based passivating contacts on the rear side are fabricated and characterized. The scientific approach used, and the insights presented in this work,  help to understand the mechanisms and behavior of screen-printed and fired-through contacts to polysilicon layers deposited onto textured silicon surfaces.